A Critical Analysis of the American Immigration Policy and the Erosion of the American Dream - آمال دركي; منال قعري (University of Eloued جامعة الوادي, 2025)
الملخص: تهدف هذه الدراسة لتحديد العلاقة الكامنة بين تبدد الحلم الأمريكي وسياسات الهجرة في أمريكا ،من خلال تحليل التغييرات الحالية في السياسات حول المفاهيم الاقتصادية الكامنة به بناء على ما استجد من سياساتها. كون هذه الأخيرة تسعى لدحض فرص العديد من المهاجرين في تحقيق رقيهم الاقتصادي والاجتماعي بتهميشهم من أسس وقيم هذا الحلم. غير ان هذه السياسات التقييدية ساهمت في نقص فرص العديد من المهاجرين لتحقيقه، لا سيما اجتماعيا واقتصاديا. تعتمد الدراسة منهجا بحثيا مدمجا لتحليل هذه الظاهرة بشكل نقدي، مع التركيز على تطور سياسات الهجرة خلال الفترة الممتده من عام 2000 الى عام 2022. كما تأخذ الدراسة بعين الاعتبار السياق التاريخي للهجرة الى الولايات المتحدة، بدءا من الهجرات الأوروبية المبكرة وصولا إلى تنوع المجتمعات المهاجرة المعاصرة، بهدف تقديم اعمق لتغير سياسات الهجرة بمرور الزمن. وتظهر النتائج ان السياسات الصارمة قد أثرت بشكل كبير على قدرة المهاجرين في الوصول الى فرص العمل والاستقرار الاقتصادي وتحقيق الحلم الأمريكي، حيث كشفت النتائج النوعية عن صراعات نفسية واجتماعية يعاني منها المهاجرون، بينما أظهرت النتائج الكمية تراجعا ملحوظا في فرص التوظيف والترقي الاجتماعي. وبشكل عام، تسهم هذه الدراسة في تقديم فهم شامل لتأثير هذه السياسات على تقليص قدرة المهاجرين على تحقيق الحلم الأمريكي. Abstruct: This research investigates the relationship between U.S. immigration policies and the erosion of the American Dream. It aims to explore how the current changes in the United States’ foreign policies have affected its ideals, socio-economic opportunities, inclusivity and upward mobility in the light of the restrictiveness of immigration policies. Subsequently, it examines how current political decisions have contributed to the eradication of this symbol. On these premises, a mixed methods approach was employed to critically analyze the development of immigration policies from 2000 to 2022 and their impact on the American Dream. Moreover, the analysis incorporates the historical context of U.S. immigration, from early European migration to today’s diverse immigrant groups, to provide a deeper understanding of how immigration patterns have evolved over time. The study, whose findings reflect immigrants’ personal experiences and challenges as well as their opportunities through highlighting the measurable impact of stricter policies, yielded both qualitative and quantitative results. Subsequently, the former demonstrates how immigrants face emotional and social struggles navigating the system, while the latter shows significant declines in economic opportunities, employment access and upward mobility. Overall, this research contributes a comprehensive understanding of how restrictive immigration policies have significantly limited immigrants’ ability to achieve the American Dream
Master's Degree In Literature and Civilization
Keywords: American Dream; Erosion; Immigration; Policies.